Zewnętrzne ślady pamięciowe społeczności paleolitycznych - Wagner, Patrycja (Folia Praehistorica Posnaniensia, 2024)
This article explores the Paleolithic era through the lens of art and memory. Specifically, it focuses on the memory category, particularly the memory trace/ engram, to better understand the role that Paleolithic art may have played for communities during that time. Paleolithic art can be seen as a kind of memory trace, carrying information and knowledge about behaviors and actions that were transmitted through it. The deliberate placement of images in an external environment was a significant milestone in the cultural and social evolution of hominids.